Modulation of the structural and functional properties of perilla protein isolate from oilseed residues by dynamic high-pressure microfluidization. (15th December 2021) - Zhao, Qiaoli; Yan, Weiqiang; Liu, Yuanfa; Li, Jinwei
Highlights: DHPM treatment reduced the particle size and absolute zeta potential of PPI. DHPM treatment induced the changes of structure caharacteristics of PPI. DHPM treatment improved the functional properties of PPI. DHPM has a potential to be introduced as a novel processing method in PPI industry. Abstract: Dynamic high-pressure microfluidization (DHPM) is an alternative method to physically modify proteins to improve their functional properties. In this study, perilla protein isolate (PPI) was treated by DHPM at different pressures. Results showed that DHPM treatment reduced the particle size and absolute potential of PPI by 75.90% and 22.28%. The increased surface hydrophobicity and free sulfhydryl content were observed in DHPM-treated PPI, which may be caused by the comformation changes of PPI. Furthermore, DHPM treatment would not cause the degradation of the main subunits and the variation of crystalline regions in PPI, but enhancing the thermal stability of PPI at 90 MPa and 120 MPa. Functional properties analysis indicated that DHPM treatment at 120 MPa was more effective in improving the solubility, foaming and emulsifying capacities of PPI. The results suggested that DHPM can be used to enhance the functional properties of PPI and expand its application in food systems.